2019
DOI: 10.1002/aoc.5015
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of cytotoxicity, antioxidant, antibacterial, antifungal, and cutaneous wound healing properties of gold nanoparticles produced via a green chemistry synthesis using Gundelia tournefortii L. as a capping and reducing agent

Abstract: The exploitation of various plant materials for the biosynthesis of nanoparticles is considered a green technology because it does not involve any harmful chemicals. The aim of the experiment was chemical characterization and evaluation of cytotoxicity, antioxidant, antibacterial, antifungal, and cutaneous wound healing activities of gold nanoparticles using aqueous extract of Gundelia tournefortii L. leaves (AuNPs@GT). These nanoparticles were characterized by fourier transformed infrared spectroscopy (FT‐IR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 46 publications
(68 reference statements)
8
100
0
Order By: Relevance
“…In the previous study was revealed that gold nanoparticles have strong antioxidant activities against free radicals such as DPPH. In the previous study, there weren’t significant differences between gold nanoparticles and BHT as a positive control …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In the previous study was revealed that gold nanoparticles have strong antioxidant activities against free radicals such as DPPH. In the previous study, there weren’t significant differences between gold nanoparticles and BHT as a positive control …”
Section: Resultssupporting
confidence: 93%
“…Many studies have revealed that antioxidant compounds remove the free radicals of hematotoxic substances and prevent their toxic effects . Also, many studies similar to our study, indicated remarkable antioxidant effects of gold nanoparticles …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…They try to combine nanotechnology with medicine for the synthesis of these drugs . Among various nanoparticles, synthesized gold nanoparticles using plant extracts have recently received much consideration . Recently, scientists have tried to survey the therapeutic potentials of gold nanoparticles especially in the treatment of various cancers.…”
Section: Introductionmentioning
confidence: 99%